Critical community psychology - Kagan, Carolyn; British Psychological Society (Chichester, West Sussex : BPS Blackwell/John Wiley, 2011)
Interest in community psychology, and its potential has grown in parallel with changes in welfare and governmental priorities. Critical Community Psychology provide students of different community based professions, working in a range of applied settings, at both undergraduate and postgraduate levels, with a text which will underpin their community psychological work. Clear learning objectives and chapter contents outlined at the start of each chapter. Key terms highlighted with definitions, either as marginal notes or in chapter glossaries. Case examples of community psychology in action. Each chapter ends with a critical assessment section. Discussion points and ideas for exercises that can be undertaken by the reader, in order to extend critical understanding. Lists of further resources -- e.g. reading, film, electronic. Authors are members of the largest community psychology departmental team in Europe'--Provided by publisher.
Machine generated contents note: -- Critical community psychology in Manchester -- What is critical community psychlology? -- Core elements of a critical community psychology -- The contested nature of community -- Community as social ties -- Problem definition -- Action planning -- Action 1: furtherance of critical consciousness and creation of new forms of social settings -- Action 2: Development of alliances, and accompaniment, advocacy and analysis of policy -- Evaluation -- Change, influence and power -- Roles, skills and reflections on learning for community psychologists -- Critical disruption: Does critical community psychology have an adequate praxis?
Includes bibliographical references and index.
Keywords: Community Mental Health Services -- methods -- England; Community Psychiatry -- England; Critical Care -- methods -- England